1995
DOI: 10.3109/13590849509008762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molybdenum on Pain and General Health: A Pilot Study

Abstract: Fourteen people graded their aches and pains and general health for 28 days. They then took either up to 500 p g of molybdenum as amino acid chelate per day, or placebo for the next 28 days, while they continued their records. The groups were crossed over for a third 28-day period. Their aches and pains improved on molybdenum (signijcant at the 0.05 level). Their general health also improved on molybdenum (signijicant at the 0.025 level). Suggestions are made for categories of people who may benejt from molybd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The salt from this species yielded by far the highest contents of molybdenum (700 ppm); some studies (cf. Moss, 1999) have shown that molybdenum has an important function in relieving aches and muscular pains.…”
Section: Ash Salts For the Witotomentioning
confidence: 99%
“…The salt from this species yielded by far the highest contents of molybdenum (700 ppm); some studies (cf. Moss, 1999) have shown that molybdenum has an important function in relieving aches and muscular pains.…”
Section: Ash Salts For the Witotomentioning
confidence: 99%
“…The Mo food consumption is recommended for infants (0.015–0.04 mg/day) and all individuals ≥10 years old (0.025–0.15 mg/day) [ 63 ]. The health benefit of Mo is correlated with toxicity prevention by several metabolites, reduction in aerosol organs irritability, night blindness, neurological damage, aches and pain [ 64 , 65 , 66 ]. The Mo concentrations of this pulp are between those of pea seeds and tomato (0.10–0.20 mg/100 g) [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The health benefit of Mo is correlated with toxicity prevention by several metabolites, reduction of aerosol organs irritability, night blindness, neurological damage, aches and pain [59][60][61]. The Mo concentrations of this pulp are between pea seeds and tomato (0.10-0.20 mg/100 g) [62].…”
Section: The Mineral Concentration In Pulp Collected In Three Differe...mentioning
confidence: 99%